Investigating the Effect of Internal Audit on the Performance of Private Banks' System - Mahdi Salehi; Arash Arianpoor; Fatemeh Salehi (Journal of Accounting, Business and Management (JABM), 2013)
Internal controls result in increased effectiveness, decreased risk of losing assets, rational ensuring of financial statements' reliability and respecting to rules and regulations. To this end, demand for better and superior systems for internal controlling and their performance report is increasing continuously. In this research, the effect of internal audit on the performance of private banks' systems in Iran is investigated. The results show that, internal audit affects private banks' systems. In addition, internal audit of Private Banks has a good rank in effectiveness but does not do its duties without siding and with impartiality. Among the results of the research is the important role of internal audit objects to achieve effectiveness. As such, management's enough recognition of internal audit importance and its performance and responsibilities results in the effectiveness of internal audit.